The Analysis Methodic of Working Capital - Mackevičius, Jonas; Poškaitė, Dalia (Ekonomika, 2000)
The article is devoted to the methodology of analysis of working capital. In the article we also examine some of the basic conceptual items related to Working capital. Working capital is one of the most important indicators of financial statement of the enterprise. Working capital policy involves the management of the current assets of the firm j:md acquisition of the appropriate financing for those assets. Working Capital could be calculated in two ways: 1) as difference between current assets and current liabilities 2) as difference between owner’s equity plus long - term liabilities and long - term assets. Typical working capital decisions involve a determination of the appropriate levels of cash. accounts receivable, and inventory that the firm should main tain. On the financing side, must be determined wether to carry these assets through credit extension from the supplier, short term bank loans, or longerterm credit arrangement. On the data basis of real existing enterprise the analysis of working capital amount, dinamics, structure. flexibility were performed. Also was performed analysis of factors influenced on the deviation of working capital.